ФІНАНСОВА БЕЗПЕКА ТЕРИТОРІАЛЬНИХ ГРОМАД В УКРАЇНІ: СУТНІСТЬ, СТРУКТУРНІ СКЛАДОВІ, ЗАГРОЗИ (Світ фінансів, 2019)
Бак Н. А. Фінансова безпека територіальних громад в Україні: сутність, структурні складові, загрози.Науково обґрунтовано авторський підхід щодо змісту, структурних складових фінансової безпеки територіальних громад, а також її функціональної ролі в системі фінансової безпеки територій і держави. Охарактеризовано фінансові інтереси територіальних громад. Наголошено на відповідальності органів влади різних рівнів за реалізацію фінансових інтересів і формування безпечного середовища функціонування територіальних громад. До структурних складових фінансової безпеки територіальних громад віднесені бюджетна, податкова, боргова та інвестиційна. Проаналізовано та систематизовано основні загрози фінансовій безпеці територіальних громад, які супроводжують процес бюджетної децентралізації. Бак Н. А. Финансовая безопасность территориальных общин в Украине: сущность, структурные составляющие, угрозы.Научно обоснован авторский подход относительно сущности, структурных составляющих финансовой безопасности территориальных общин, а также ее функциональной роли в системе финансовой безопасности территорий и государства. Охарактеризованы финансовые интересы территориальных общин. Отмечена ответственность органов власти разных уровней за реализацию финансовых интересов и формирование безопасной среды функционирования территориальных общин. К структурным составляющим финансовой безопасности территориальных общин отнесены бюджетная, налоговая, долговая и инвестиционная безопасность. Проанализированы и систематизированы основные угрозы финансовой безопасности территориальных общин, которые сопровождают процесс бюджетной децентрализации. Bak N. Financial security of territorial communities in Ukraine: content, components, threats.Introduction. The process of fiscal decentralization contributes to the transformation of territorial communities and local authorities into full-fledged members of the system of financial inter-connections. Territorial communities have individual financial interests. The need to protect them is at the heart of creating a safe environment for the functioning of territorial communities. However, financial security of territorial communities as separate economic units is not given enough attention to Ukraine. Instead, a more general notion is explored which isfinancial security of the regions.Purpose– theoretical substantiation of author's view on the content and structural components of the financial security of territorial communities, its place in the system of financial security of territories and the state as well as systematization of main threats to the financial security of communities in the context of implementing the budget decentralization policy.Results. The definition of financial security of territorial communities is substantiated. It is based on the protection of the financial interests of territorial communities. The features of financial interests of territorial communities are derived. Components of financial security of territorial communities are characterized. These include budget, tax, debt and investment security. The main threats to the financial security of territorial communities are analyzed and systematized. They are a result of imperfect institutional environment for local self-governments and the integration of territorial communities as subjects of a single (national) economic system. Furthermore, the threats are connected to the peculiarities of the territorial economy, communal infrastructure, the level of public consciousness and financial responsibility of heads of local self-overnment bodies.Conclusions.The financial security of territorial communities should be investigated as a part of the financial security of regions. Achieving a desirable state in practice requires synergy with the financial security of households and business entities located on the territory concerned. It is also necessary to seek coordination of financial interests of various territorial ommunities and the state as a whole.Local governments and central authorities are responsible for creating a safe financial environment for the functioning of territorial communities during budget decentralization. It is necessary to improve the mechanism of inter-territorial redistribution of financial resources.The list of potential threats to the financial security of territorial communities should be identified in the process of strategic development of territories and the use the SWOT-analysis for this purpose.